Strategi Penguatan Karakter Gotong Royong Melalui Tema Berkebhinekaan Global Pada Peserta Didik SD Negeri Joglo 76 Surakarta - Al Karimah, Widya; Liestyasari, Siany Indria (Jurnal Noken: Ilmu-Ilmu Sosial, 2025)
The limited interaction during the pandemic and the phenomenon of learning loss gave birth to a transformation of the mutual cooperation character of students. Through the Pancasila Student Profile Strengthening Project (P5), a strategy is needed to optimize the achievement of character dimensions and learning objectives. Based on a qualitative method through a case study approach with Vygotsky's Zone of Proximal Development (ZPD) theory, this study was conducted to determine the strategies implemented by schools and teachers in strengthening the mutual cooperation character with P5 Global Diversity Theme. Data were collected and analyzed using purposive sampling techniques through Miles and Huberman analysis, this study involved the Deputy Head of Curriculum as the designer of P5 activities, a team of facilitators and driving teachers as those responsible for P5 and students as learning subjects. The results of the study showed that the roles of teachers, peers, and parents were actively involved in implementing the mutual cooperation strengthening strategy. This strategy is realized through theme planning and project mapping, providing assistance (scaffolding) and reducing the intensity of scaffolding, and evaluation with assistance differentiation analysis to encourage students to achieve their actual mutual cooperation potential.